(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Substance abuse is considered an international public health concern but can be difficult to treat. In this field,cognitive behavioral therapies - such as Schema Therapy (ST) - have been increasing in notoriety. Research studies have associated its basic construct – early maladaptive schemas (EMS) – to substance abuse and dependence. Therefore, the present study conducted a systematic literature review of the last 20 years in order to investigate national and international research studies that evaluated the prevalence of EMS in this population. Twenty-five studies, most of them international, were identified and analyzed according to their results, design, sample, authorship, publication year and country of origin. Despite the differences found in schemas prevalence between the samples, a common conclusion is that EMS are important predisposing factors for addictive behavior. Finally, it was discussed that further research related to ST efficacy in the treatment of substance use disorders is warranted.